Impact of Co on the Ni0.9Co0.1-Ge0.9Sn0.1 Solid-State Reaction and Properties. (22nd October 2019) - Quintero, Andrea; Gergaud, Patrice; Hartmann, Jean-Michel; Reboud, Vincent; Cassan, Eric; Rodriguez, Philippe
Abstract : A systematic and comprehensive study concerning the solid-state reaction between Ni0.9 Co0.1 and Ge0.9 Sn0.1 layers was carried out. Special attention was paid on the impact of adding 10 at.% of Co in the Ni metallization layer. In-situ X-ray Diffraction (XRD), atomic force microscopy (AFM) and Sheet resistance (Rsh ) measurements were performed in order to follow the solid-state reaction, surface morphology and electrical properties evolution, as the temperature increases.